RESPONSE OF MUSLIM INTELLECTUAL GROUPS TO DUTCH COLONIAL EDUCATION IN THE EARLY 20TH CENTURY - Ahmad Sirfi Fatoni (PT. Jurnal Center Indonesia Publisher, 2026)
Islamic Education and Colonial Education are two methods to educate the Indonesian people, especially in Java. Islamic Education and Colonial Education have their own advantages for society. Islamic Education tends to be more religious, while Colonial Education tends to be secular and liberal. Each education has a different teaching system because it has different goals and targets according to the interests of the government in power at that time. This research method uses a historical method that is based on four things as usual, namely: heuristics, criticism, verification and historiography. Because this event is a political history, the researcher uses a socio-political approach to analyze it. On the other hand, assisted by the challenge and response theory developed by Arnold Toynbe. According to this theory, culture occurs because of challenges and answers between humans and their surroundings. The results of this study indicate that the existence of racial and discriminatory Dutch colonial government education resulted in the emergence of forms of resistance in the field of education. This phenomenon results in the birth of Islamic boarding schools and private schools such as: Tebu Ireng Islamic Boarding School (1899), Tambak Beras Islamic Boarding School (1919) East Java, Krapyak Islamic Boarding School, Yogyakarta (1911), Sukamanah Islamic Boarding School, Cipasung Tasikmalaya, West Java (1930). As for private schools (private) namely Muhammadiyah School (1912), Taman Siswa (1922) and Nahdlatul Ulama (1926).